Faktor-Faktor Yang Mempengaruhi Pertumbuhan Deposito Mudharabah Pada Bank Umum Syariah (BUS) (Periode 2010-2015) - S.N, Clarieszafanie, Ir, Maulidyah, MS (2016)
ABSTRACT Fluctuating economy situation become an important indicator for investor to make a decision to investment.because as an investor will act based minimum risk for investment to achieve profit.this research intented to analyze the influence of the financing to deposit ratio (FDR),Non Performing Finance(NPF),inflation to mudharabah deposito. Data type for this research is time series periode 2010:7-2015:3. To find out the good influence for the short term or the long term. Methods of analysis for this research is error correction mode (ECM).this research result indicate as partial in short term Non performing finance (NPF) and a negative effect to mudharabah deposito due inflation. while significant negative effect to mudharabah deposito caused by financing to deposit ratio(FDR), in long term as partial NPF and FDR take a significant positive effect to mudharabah deposito, and inflation take a significant negative effect to mudharabah deposito.simultaneously NPF,FDR and inflation influence to mudharabah deposito. Keywords:mudharabah deposito, non performing financing(NPF), financing to deposit ratio (FDR), inflation.